The utility of cerebral oxygenation monitoring in premature neonates - Nesargi, Saudamini; Nitsch, Alexander; Wolf, Martin (Journal of Medical Science, 2020)
Near-infrared spectroscopy allows the measurement of cerebral oxygenation in preterm infants. This study aimed to demonstrate several highly relevant clinical situations in preterm infants in which the standard set of monitoring parameters without near-infrared spectroscopy is not sufficient to detect possible adverse situations, possibly resulting in severe complications, i.e. adverse neurological outcomes. The examples include situations of low blood pressure, persistent open ductus arteriosus, malfunctioning autoregulation of the brain oxygenation, and periods of irregular breathing. Without near-infrared spectroscopy, it is impossible to determine whether such a situation imposes any risk for the brain, whereas the measurement of cerebral oxygenation as an additional source of information enables the clinician to recognise these conditions and modify treatment or use countermeasures to protect the patient from brain damage and ensuing lifelong disabilities.
Keywords: NIRS; near-infrared spectroscopy; preterm; neonate; neonatology; cerebral oxygenation